1991
DOI: 10.1099/00221287-137-10-2439
|View full text |Cite
|
Sign up to set email alerts
|

The thn mutation of Schizophyllum commune, which suppresses formation of aerial hyphae, affects expression of the Sc3 hydrophobin gene

Abstract: The spontaneous and recessive mutation thn in the basidiomycete Schizophyllum commune suppresses the formation of aerial hyphae in the monokaryon and, if present as a double dose, the formation of both aerial hyphae and fruit-bodies in the dikaryon. In the monokaryon, the mutation prevents accumulation of mRNA of the Sc3 gene, and in the dikaryon it also prevents the accumulation of fruiting-specific mRNAs, including mRNAs of the Scl and Sc4 genes, which are homologous to the Sc3 gene. These three genes code f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 23 publications
1
80
0
2
Order By: Relevance
“…The 14.5-kDa protein, HsbA, can bind to PBSA and recruit cutinase CutL1. HsbA does not contain any cysteine residues, so it is not formally classifiable as a hydrophobin (3,31,32). Genes orthologous or paralogous to hsbA in other fungi are known (EAL94060, EAL84331, EAA58613, and AAB69331), but none of the orthologues have been functionally characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The 14.5-kDa protein, HsbA, can bind to PBSA and recruit cutinase CutL1. HsbA does not contain any cysteine residues, so it is not formally classifiable as a hydrophobin (3,31,32). Genes orthologous or paralogous to hsbA in other fungi are known (EAL94060, EAL84331, EAA58613, and AAB69331), but none of the orthologues have been functionally characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The Sc3p of S. commune aggregates on the aerial hyphae as SDS-insoluble complexes (Wessels et al, 1991 a), and cryparin and cerato-ulmin have been shown to be present in the cell walls of aerial hyphae of C. purusitica and 0. ulrni, respectively, by immunofluorescent microscopy (Carpenter et al, 1992) and immunoelectron microscopy (Svircev et al, 1988). S. commune Sc3p has been shown to be secreted from the tips of the submerged hyphae (Wosten et al, 1994a) but the cell walls of submerged hyphae, however, were reported to lack Sc3p.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobic amino acids are shown below and hydrophilic amino acids above the x-axis. The amino acids of the hydrophobins, including the signal sequences, are shown along the x-axis like protcins were searched for by comparing the properties of a protein with those described for hydrophobins (Wessels et al, 1991 a ;Wosten el al., 1993;Carpenter et al, 1992). To verify if one of the hydrophobin-like proteins was HFBI, the hjb/ gene was cxpressed in E. coli as a FLAG fusion (see Experimental Procedures), and antibodies were prepared against the fusion protein (Fig.…”
Section: Localization Of the Hfbi Proteinmentioning
confidence: 99%
“…Other potential components include cysteinerich, ca. 30-kDa "hydrophobins" which have been isolated from the outer surface of Schizophyllum commune and Aspergillus nidulans (41,42) but have yet to be identified or characterized in C albicans.…”
Section: Discussionmentioning
confidence: 99%